2015
DOI: 10.5664/jcsm.5282
|View full text |Cite
|
Sign up to set email alerts
|

Technology Use and Sleep Quality in Preadolescence and Adolescence

Abstract: Study Objectives: The purpose of this study was to analyze differences between preadolescents and adolescents on the use of technology and to test the contribution of using Internet and mobile phone, and circadian preference on sleep quality. Methods: We recruited a sample of 850 (364 males) preadolescents and adolescents. Self-report questionnaires about sleep schedule, sleep wake behavior problems, circadian preferences, and the use of technology (e.g., Internet and mobile phone) were administered. Students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 49 publications
10
107
0
10
Order By: Relevance
“…The authors concluded that evening circadian preference, mobile phone and Internet use, the number of other activities engaged in after 9:00 PM, later media turning-off time, and the number of devices in the bedroom have different, but significant, negative influences on sleep quality in preadolescents and adolescents. 90 Similarly, Lemola et al 99 reported associations between electronic media use in bed before sleep, sleep difficulties, and symptoms of depression in teenagers.…”
Section: How Does Media Use Affect Sleep?mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that evening circadian preference, mobile phone and Internet use, the number of other activities engaged in after 9:00 PM, later media turning-off time, and the number of devices in the bedroom have different, but significant, negative influences on sleep quality in preadolescents and adolescents. 90 Similarly, Lemola et al 99 reported associations between electronic media use in bed before sleep, sleep difficulties, and symptoms of depression in teenagers.…”
Section: How Does Media Use Affect Sleep?mentioning
confidence: 99%
“…90 Increased duration of media exposure and the presence of a TV, computer, or mobile device in the bedroom in early childhood have been associated with fewer minutes of sleep per night, especially among children of racial/ethnic minority groups. 91 Later bedtimes after evening media use and violent content in the media also may be contributing factors, 92 and suppression of endogenous melatonin by blue light emitted from screens is another possible cause.…”
Section: How Does Media Use Affect Sleep?mentioning
confidence: 99%
“…4), including poor sleep quality Arora et al, 2012;Bruni et al, 2015;Hysing et al, 2015;Lemola et al, 2014;Liu et al, 2017;Mak et al, 2014;Sami et al, 2018;Hawi et al, 2018), early awakenings (Arora et al, 2014;Fatih et al, 2013;Choi et al, 2009;Shochat et al, 2010), difficulty falling asleep (Arora et al, 2014;Fatih et al, 2013;Choi et al, 2009;Shochat et al, 2010), night awakenings (Arora et al, 2014;Fatih et al, 2013;Choi et al, 2009), less sleep quantity ( Van den Bulck, 2004;Nuutinen et al, 2014;Park, 2014;Park & Lee, 2017;Punama-ki et al, 2006;Shochat et al, 2010;Kim et al, 2018) and insomnia (Cheung & Wong, 2011;Tan et al, 2016;Tamura et al, 2017). Three subgroups were classified by country.…”
Section: Sleep Problemsmentioning
confidence: 99%
“…There were data from 22 studies Arora et al, 2012;Arora et al, 2014;Bruni et al, 2015;Fatih et al, 2013;Cheung & Wong, 2011;Choi et al, 2009;Hysing et al, 2015;Van den Bulck, 2004;Lemola et al, 2014;Liu et al, 2017;Mak et al, 2014;Nuutinen et al, 2014;Park, 2014;Park & Lee, 2017;Punama-ki et al, 2006;Shochat et al, 2010;Tan et al, 2016;Sami et al, 2018;Tamura et al, 2017;Hawi et al, 2018;Kim et al, 2018) that investigated association between the technology use and sleep problems (Fig. 4), including poor sleep quality Arora et al, 2012;Bruni et al, 2015;Hysing et al, 2015;Lemola et al, 2014;Liu et al, 2017;Mak et al, 2014;Sami et al, 2018;Hawi et al, 2018), early awakenings (Arora et al, 2014;Fatih et al, 2013;Choi et al, 2009;Shochat et al, 2010), difficulty falling asleep (Arora et al, 2014;Fatih et al, 2013;Choi et al, 2009;Shochat et al, 2010), night awakenings (Arora et al, 2014;Fatih et al, 2013;…”
Section: Sleep Problemsmentioning
confidence: 99%
See 1 more Smart Citation